Witness Protection in Law Enforcement Against Organized Narcotics Cases - Sindi Lestari; , Miranda Einilia; Saidatul Husna Harahap (ISNU Sumatera Utara, 2024)
Witnesses play a crucial role in the criminal justice system, particularly in uncovering organized narcotics crimes, where their testimony often becomes the primary evidence for law enforcement. However, witnesses in organized narcotics cases are highly vulnerable to intimidation, threats, and retaliation from criminal syndicates, making legal protection essential to ensure their safety and willingness to testify. This study aims to examine the forms of legal protection provided to witnesses in organized narcotics cases and to analyze the role of the Witness and Victim Protection Agency (LPSK) in safeguarding witnesses throughout the criminal justice process. This research employs an empirical legal research method by combining field research through interviews with officials of the Medan Representative Office of the Witness and Victim Protection Agency and a literature review of statutory regulations, books, and scientific journals. The findings indicate that witness protection is implemented through three primary mechanisms: physical protection, including police security, safe houses, and identity changes; legal protection, including immunity from legal retaliation and special treatment for justice collaborators; and the fulfillment of procedural rights, such as legal assistance, information on case developments, transportation, medical treatment, psychological rehabilitation, and living expenses during the protection period. The study also finds that justice collaborators play a strategic role in exposing organized narcotics networks by providing crucial information that enables law enforcement authorities to identify and prosecute the principal offenders. Therefore, comprehensive witness protection is indispensable for ensuring effective law enforcement, protecting human rights, and improving the successful prosecution of organized narcotics crimes in Indonesia.